Indução a espermiação do mandi-pintado, Pimelodus britskii no período reprodutivo (Teleostei: Pimelodidae) - Damasceno, Danielle Zanerato [UNESP] (2014)
The aim of this study was to characterize the semen Pimelodus britskii through different collection methods and hormonal doses. The experiment was run in two reproductive periods, November/2011 to March/2012 and October/2012 to March/2013. In the first breeding season (Experiment 1 ) in all months 12 fish were divided into two groups, one experimental group with Carp Pituitary Extract - EHC (3.0 mg.kg- 1) and a group without hormonal induction, after 240 units accumulated thermal-UTA fish from both groups were euthanized and had their macerated testes. In the second reproductive period (Experiment 2 ) 30 fish were divided into five groups for comparison of different doses of human Chorionic Gonadotropin-hCG and EHC in spermiation (T1: Control, T2: 3,0mg.kg-1 EHC, T3: 0,5 mg.kg-1 +3,0 mg.kg-1 EHC , T4: 0,5 mg.kg-1 +7,0 mg.kg-1 EHC , T5: 200UI.kg-1 hCG ) , and in this period the same fish were used every month, and after 240 UTA semen was collected by abdominal massage. Motility and sperm velocity were evaluated through the CASA software (Computer Assisted Sperm Analysis). The seminal variables using Statistica 7.0. Through the soaking, there was color change (white to yellow), pH (6 to 7) and sperm concentration (11,9x109±4,16x109 to 9,15x109±3,55x109 spermatozoa/mL-1). The volum months showed relationship between treatments (p<0,05). For all copies motility was higher in November/2011, decreasing gradually until February/2012. The same occurred with the values of the IGS (p<0,05), showing the action of hormonal induction in seminal volume ...